HUBUNGAN ANTARA KECERDASAN SPIRITUAL IBU, SOSIALISASI MORAL, INTERAKSI IBU-ANAK, DAN KARAKTER TEKUN ANAK USIA SEKOLAH PADA KELUARGA DI SLUM AREA. - Alfiasari, Alfiasari (Jurnal Penelitian Kesejahteraan Sosial, 2019)
The persistent character formed is inseparable from the parents factor, such as mother’s spiritual intelligence, moral socialization, and mother-child interaction. The objectives of this research are to: (1) identify and analyze the relationship between family and child characteristics, motherâ€™s spiritual intelligence, moral socialization, and mother-child interaction with children’s persistent character in urban slum area. This study used cross-sectional study design and purposive location selection. Respondents of this study included 44 mothers and 44 children aged 8-12 years who attend formal school, and live in slums in one area of North Jakarta. The average achievement of the mother’s spiritual intelligence, moral socialization, and mother-child interaction, and the persistent character of the children based on the index are categorized as good enough. The results of the correlation test indicate that large of family, motherâ€™s spiritual intelligence, moral socialization, and mother-child interaction had positively correlation with the persistent character of school age children. A significant positive relationship also occurs between spiritual intelligence and moral socialization. The mother-child interaction with moral socialization and motherâ€™s spiritual intelligence also showed a very significant relationship.Â